Optimization of techniques for the extinction and prevention of coal fires produced in final walls as a result of spontaneous combustion in the Cerrejón mine—Colombia - Bustamante Rúa, Moisés O; Bustamante Baena, Pablo; Daza Aragón, Alan J (Environmental science and pollution research international, 2018)
The Cerrejón mine has identified fires in its coal production seams for a few years in its operation. Fires are produced as a result of spontaneous combustion phenomena. Coal spontaneous combustion is a phenomenon that occurs naturally during coal oxidation when exposed to atmospheric conditions, due to erosion processes, geological and mining practices. This phenomenon is a subject of great concern in the world’s coal mines, as it causes environmental problems, generating emissions of polluting gases into the atmosphere and economic losses due to reserve consumption. In this work, we seek to optimize the prevention and extinction processes used by the company. In terms of prevention, the current state was evaluated and alternatives, such as diluted bitumen and brine (combustion inhibitor), cement/slaked lime, fine sand cement, and clinker/slaked lime were developed to avoid ignition. As far as extinction is concerned, an additional methodology for medium magnitude fires was determined, in order to improve extinction times through the use of cooling. It was determined that the bitumen/brine has better adhesion and durability properties in the coal seam. Extinction through reagent cooling is quicker, thus improving the backhoe’s productivity and minimizing costs.